PENGARUH KESEIMBANGAN KEHIDUPAN KERJA, STRES KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT. GEO GIVEN VISI MANDIRI SIDOARJO - Zamzami Murfid; Sri Budi Kasiyati (Cahaya Ilmu Bangsa, 2024)
Indonesia is a country that is developing rapidly, of course in the infrastructure sector. Every government agency, company and organization has goals to achieve their desires. In order to achieve a desire, a government agency must have human resources to organize and manage a goal within an agency. In the world of work, especially in government agencies, employees cannot be separated from the regulations that have been set or compiled by a government agency. This research is based on existing phenomena. Objectiveof this research is to find out and get a study about the influence of Communication, Teamwork, and career development on Work Morale employees of the Gresik Regency Housing and Settlement Areas Department of Human Settlements. This research is quantitative research with a sample size of 58 employee respondents. To carry out the analysis using the help of the SPSS program version 26 (Statistics Product and Service Solution). Based on the analysis results, the f test is used to test the magnitude of the influence of all independent variables consisting of Communication (X1), Teamwork (X2), and Career Development (X3), together on the dependent variable Work Morale (Y). Basis for decision making F test, namely by comparing the significant value or calculated F value with the F table. The results of hypothesis testing stated that the simultaneous test obtained a significant value of 0.000 < 0.05 and F_count of 5.881 > F_table 2.77. This shows that Communication (X1), Teamwork (X2), and Career Development (X3) simultaneously have a significant effect on Work Morale (Y).